2016
DOI: 10.3892/ol.2016.4408
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related inflammatory pseudotumor of the kidney mimicking renal cell carcinoma: A case report

Abstract: Abstract. IgG4-related disease is a recently recognized clinical entity. It is characterized by diffuse organ swelling or mass formation, a dense lymphoplasmacytic infiltrate rich in IgG4-positive plasma cells with fibrosis and typically an increased serum IgG4 concentration, which may affect various organs. An 80-year-old woman with an otherwise unremarkable previous medical history was revealed to have a renal mass that was indicative of renal malignant carcinoma, for which a radical nephrectomy was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…Using diffusion-weighted magnetic resonance imaging (MRI), a recent study reported 100% sensitivity with respect to computed tomography (CT)[ 45 ]. However, a caveat is that when a solid mass is observed, it may be misdiagnosed as a malignant neoplasm and lead to an unnecessary nephrectomy[ 46 , 47 ].…”
Section: Igg4 Related Tinmentioning
confidence: 99%
“…Using diffusion-weighted magnetic resonance imaging (MRI), a recent study reported 100% sensitivity with respect to computed tomography (CT)[ 45 ]. However, a caveat is that when a solid mass is observed, it may be misdiagnosed as a malignant neoplasm and lead to an unnecessary nephrectomy[ 46 , 47 ].…”
Section: Igg4 Related Tinmentioning
confidence: 99%
“…Es una lesión que mimetiza a un carcinoma renal y resulta una forma de presentación de la enfermedad sumamente inusual, con menos de cinco casos reportados en la literatura hasta el día de hoy 51 . Es difícil diferenciar entre un pseudotumor renal secundario a ER-IgG4 y una lesión maligna basándonos solo en los estudios de imagen 52 .…”
Section: Pseudotumor Renalunclassified
“…La resonancia magnética puede mostrar tumores renales isointensos o hipointensos en T1, e imágenes hipointensas en T2, y mostrar realce homogéneo tras la administración de medio de contraste 53 . El diagnóstico diferencial definitivo lo dará una biopsia, y el tratamiento será mediante corticoesteroides, con los cuales la lesión mejorará significativamente, aumentando la función renal y disminuyendo la concentración de IgG4 circulante 51 .…”
Section: Pseudotumor Renalunclassified
“…It is important to recognize IgG4-related inflammatory pseudotumor and distinguish it from renal malignant tumor to avoid unnecessary nephrectomy [162]. Another mimicker of IgG4-RKD is AAV, which can be present with elevated serum IgG4 levels and similar organ manifestations compared to IgG4-RD [163].…”
Section: Eosinophilia In Kidney Diseasementioning
confidence: 99%